The Classification, Automorphism Group, and Derivation Algebra of the Loop Algebra Related to the Nappi–Witten Lie Algebra - Xue Chen (Journal of Mathematics)
Set L≔H4⊗ℂR, R≔ℂt±1, and S≔ℂt±1/mm∈ℤ+. Then, L is called the loop Nappi–Witten Lie algebra. R-isomorphism classes of S/R forms of L are classified. The automorphism group and the derivation algebra of L are also characterized.